Monitoring of Cardiac Diseases by Use of a Wearable Sensor Platform with Capacitive ECG - Kirchner, Jens; Fischer, Georg (39th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC), 2017)
The concept of a wearable sensor platform in the form of a patch for fixation at a patient’s chest is described. It is used for monitoring of cardiac diseases, which is illustrated with the detection of atrial fibrillation.
Keywords: Wearable Sensors; Cardiac diseases; Atrial fibrillation